1992
DOI: 10.1148/radiology.184.1.1609106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hard-copy size on observer performance in digital chest radiography.

Abstract: To determine the impact of reduced hard-copy size on diagnostic performance of digital radiography, screen-film chest radiographs were compared with isodose digital storage phosphor radiographs in the detection of simulated nodules, fine pulmonary lines, and micronodular opacities superimposed on the chests of 10 healthy volunteers. Digital radiographs were laser-printed in a full-size conventional format and in image lengths of two-thirds, one-half, and five-elevenths of the conventional format. Eighteen thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Several recent articles have suggested that the small hard-copy display of CR in standard two-on-one format might be insufficient for evaluation of subtle abnormalities. 17, 18 The current study has several limitations. First, colonoscopy may not be a perfect standard, because ir has been reported that the rate of polyps missed by colonoscopy may be as high as 10% to 20%.…”
Section: Discusslonmentioning
confidence: 88%
“…Several recent articles have suggested that the small hard-copy display of CR in standard two-on-one format might be insufficient for evaluation of subtle abnormalities. 17, 18 The current study has several limitations. First, colonoscopy may not be a perfect standard, because ir has been reported that the rate of polyps missed by colonoscopy may be as high as 10% to 20%.…”
Section: Discusslonmentioning
confidence: 88%
“…As a consequence, radiologists knew the matrix size of the images beforehand, and their evaluation inevitably went along with a potential bias. Although it is unlikely that the image format represented a limiting factor for the detectability of the lesions [15], the effect of the image size on reader performance remained open. A recently published ROC study from Ueguchi and colleagues [20] focused on the detection of subtle interstitial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is only a very limited number of studies that have focused on the effects of image size and its importance for diagnostic performance. [1][2][3][4][5] Interestingly, the results of these studies are mixed.…”
Section: Introductionmentioning
confidence: 99%
“…1 The size of the images ranged from 15 × 19 to 35 × 43 cm. It was found that the interpretation accuracy varied depending on the type of lesion; while detection of nodules was not affected by image size, detection of lines and micronodular opacities declined with decreasing image size.…”
Section: Introductionmentioning
confidence: 99%